A comparison of automated and traditional monitoring techniques for marbled murrelets using passive acoustic sensors. (26th November 2015) - Borker, Abraham L.; Halbert, Portia; Mckown, Matthew W.; Tershy, Bernie R.; Croll, Donald A.
ABSTRACT: Autonomous sensors and automated analysis have great potential to reduce cost and increase efficacy of wildlife monitoring. By increasing sampling effort, autonomous sensors are powerful at detecting rare and elusive species such as the marbled murrelet ( Brachyramphus marmoratus ). New approaches must be tested for comparability to existing methodologies, so we compared the results of inland audio–visual and of automated acoustic monitoring for marbled murrelets, conducted during the 2010 breeding season, at 7 sites in the Santa Cruz Mountains, California, USA. We found automated acoustic surveys and analysis had fewer detections per morning compared with audio–visual surveyors, but the rate of automated acoustic detections per morning was positively and strongly correlated with the rate of audio–visual detections per mornings ( r  = 0.96, P  < 0.01). Furthermore, acoustic monitoring sampled 10 times more mornings per site ( x ¯  = 48) than were monitored by human surveyors ( x ¯  = 4.4) at a comparable cost. We used resampling to estimate the power to detect murrelet presence with acoustic sensors at >80% within 8 continuous days of recordings, even at low‐activity sites. Our results suggest that autonomous sensor and automated analysis approaches could greatly increase the scale and efficacy of murrelet monitoring, allowing for more cost‐effective surveying of large and remote areas of potential habitat, as well as, improved ability to measure changes in inland activity. Further study of passive acoustic recordings would be valuable to examine for acoustic signs of breeding phenology, and site occupancy, if acoustic surveys are to replace the utility of audio–visual surveys. © 2015 The Wildlife Society.